Linear Chimeric Triblock Molecules Self‐Assembled Micelles with Controllably Transformable Property to Enhance Tumor Retention for Chemo‐Photodynamic Therapy of Breast Cancer. (4th April 2019) - Liu, Rui; Yu, Meinan; Yang, Xiaotong; Umeshappa, Channakeshava S.; Hu, Chuan; Yu, Wenqi; Qin, Lin; Huang, Yuan; Gao, Huile
Abstract: Although nanoparticles are expected to revolutionize cancer treatment, their low efficacy remains the greatest limiting factor. Recent investigations found that nanoparticles' golden principle, the enhanced permeability and retention (EPR) effect, is limited by the complicated tumor microenvironment. Herein, novel transformable nanomaterials are designed to utilize the EPR effect more effectively. By tandem conjugation of the hydrophobic head (chlorin e6 (Ce6) or bilirubin (BR)), peptide to form hydrogen bond (Phe‐Phe‐Val‐Leu‐Lys (FFVLK)), and hydrophilic tail (polyethylene glycol (PEG)), chimeric molecules that can form micelles (Ce6/BR‐FFVLK‐PEG) in aqueous solution are synthesized. Notably, the spherical micelles retain shape transformability. After circulation and distribution, they respond to 650 nm laser irradiation, and morphologically change into nanofibers so as to facilitate their retention markedly inside the tumor. Upon loading a reactive oxygen species‐responsive paclitaxel dimer with thioketal linker (PTX2 ‐TK), the resultant PTX2 ‐TK@Ce6/BR‐FFVLK‐PEG nanomedicine serves as a potent chemo‐photodynamic therapeutic for cancer treatment. Evaluations at both cell level and animal level reveal that PTX2 ‐TK@Ce6/BR‐FFVLK‐PEG exhibits superior biocompatibility and biodistribution, and suppresses 82.6% of in vitro cell growth and 61.8% of in vivo tumor growth at a common dose of intravenous injection (10 mg kg −1 PTX and 3.3 mg kg −1 Ce6), becoming a novel nanomedicine with extraordinary potential in cancer therapy. Abstract : The chimeric molecules, Ce6‐FFVLK‐PEG and BR‐FFVLK‐PEG, mix and self‐assemble micelles, but morphologically change into nanofibers when receiving the 650 nm laser irradiation. The transformable property dramatically enhances nanomaterials' retention inside the tumor, which is essential for improving drug delivery efficiency, resulting in superior anticancer treatment when the nanomaterials are applied as a kind of nanomedicine.